ETHICAL LEADERSHIP AND KNOWLEDGE SHARING: THE EFFECT SELF EFFICACY - Azhar, Ali; Rahmat, Adi; Seswandi, Agus (Yayasan Education and Social Center, 2025)
Islamic boarding schools as the oldest Islamic educational institution in Indonesia are increasingly relevant considering the challenges of modernization and digitalization of education. These Islamic boarding schools must be able to maintain traditional values while adapting to the demands of modernity, including in terms of leadership and knowledge management. The purpose of this study is to Know and Analyze the Influence of Ethical Leadership on Knowledge sharing. This study uses a quantitative method approach, where the researcher formulates research problems and hypotheses as provisional answers to the questions asked. The population in this study is Ustadz and Ustadzah Teachers at Islamic Boarding Schools in Indragiri Hilir Regency with a total population of 400 people. The conclusion of this study is that the better the implementation of ethical leadership by pesantren leaders, the higher the level of self-efficacy of the ustadz and ustadzah